2020
DOI: 10.18699/vj20.638
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions of Solanum tuberosum L. associated with the tuber eye depth

Abstract: Potato (Solanum tuberosum L.) is one of the most important food crops in the world. The genome of this potato species is autotetraploid and has a high level of heterozygosity, also this potato species is a cross-pollinated plant. These characteristics complicate the genetic analysis and breeding process. The tuber’s eye depth is an important trait that affects the suitability of potato varieties for processing. Potato breeding for this trait is based on phenotypic assessment. Identification of the loci that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Two SNPs, named as c1_8019 and c2_25471, were identified as significant by the polyploid packages GWASpoly and SHEsis (Figure 6b). Previous association studies also reported these SNPs where the SNP c1_8019 is associated with potato tuber shape and eye depth traits (Rosyara et al., 2016; Sharma et al., 2018), while the SNPs c2_45606 and c2_45611 are associated with eye depth (Totsky et al., 2020).…”
Section: Resultsmentioning
confidence: 91%
“…Two SNPs, named as c1_8019 and c2_25471, were identified as significant by the polyploid packages GWASpoly and SHEsis (Figure 6b). Previous association studies also reported these SNPs where the SNP c1_8019 is associated with potato tuber shape and eye depth traits (Rosyara et al., 2016; Sharma et al., 2018), while the SNPs c2_45606 and c2_45611 are associated with eye depth (Totsky et al., 2020).…”
Section: Resultsmentioning
confidence: 91%
“…Two SNPs, named as c1_8019 and c2_25471, were identified as significant by the polyploid packages GWASpoly and SHEsis (Figure 6.b). Previous association studies also reported these SNP where the SNP c1_8019 is associated with potato tuber shape and eye depth traits [Rosyara et al, 2016, Sharma et al, 2018], while the SNPs c2_45606 and c2_45611 are associated to eye depth [Totsky et al, 2020].…”
Section: Resultsmentioning
confidence: 98%
“…Tuber eye depth is an important agronomic trait that affects the appearance and processing quality of tubers where potatoes with deep eyes contribute to significant peeling losses and are also not favoured by the consumers. To aid breeding potatoes with shallow eyes and uniform shape, several studies have been conducted in the past to identify genetic factors underlying this trait and identified a major locus controlling eye depth on chromosome 10 including minor effect QTLs on chromosomes 1, 2, 3, 4, 5, 6, 11, and 12 (Hara-Skrzypiec et al 2018 ; Li et al 2005 ; Lindqvist-Kreuze et al 2015 ; Pandey et al 2022 ; Prashar et al 2014 ; Rosyara et al 2016 ; Sharma et al 2018 ; Śliwka et al 2008 ; Totsky et al 2020 ; Zhang et al 2022 ; Zhao et al 2023 ). GWAS here detected the most significant QTL for tuber eye depth on chromosome 10 corroborating the findings from the previous studies, and additional significant QTL-MTAs were revealed on chromosomes 3, 4, 6, 7, 9, 10, 11 and 12 (Table 5 ; Figs.…”
Section: Discussionmentioning
confidence: 99%